Islamic Guidance and Counseling Practices for Strengthening Student Adjustment: A Multisite Study in Urban Modern Pesantren of Medan - Zahrah, Raudhatuz; Lubis, Lahmuddin; Sitorus, Masganti (Jurnal Pendidikan Islam, 2025)
Purpose – This study aims to examine in depth the application of Islamic counseling services in strengthening students’ self-adjustment at three Islamic senior high schools (madrasah aliyah) affiliated with modern pesantren in Medan City—MA Darul Hikmah, MA Al-Kausar Al-Akbar, and MA Ta’dib Al-Syakirin. The research focus is directed toward addressing the empirical gap concerning the effectiveness of Islamic counseling services within an urban and boarding school-based context. Design/methods/approach – Employing a qualitative approach with a multisite study design, data were collected through participatory observation, in-depth interviews, and document analysis. Informants consisted of school principals, counseling teachers, students, and parents. Data analysis was conducted thematically and across sites using the Miles, Huberman, and Saldana model. Findings – Islamic counseling services play a strategic role in strengthening students’ self-adjustment across three dimensions: social, emotional, and spiritual. The three pesantren adopt different approaches—spiritual-integrative, dialogical-reflective, and assertive-symbolic—yet share aligned objectives. The types of services include orientation, information, individual/group counseling, spiritual reinforcement, as well as evaluation and referral. Success is highly influenced by students’ personal readiness and institutional support. However, the effectiveness of these services has not yet been measured using quantitative evaluative instruments, resulting in outcome assessments that remain descriptive. Research implications – Practical implications include the need to formalize the structure of counseling services in pesantren, provide data-driven training for counseling teachers, strengthen the role of musyrif as informal mentors, and promote intensive collaboration with parents. This model is relevant for implementation in similar Islamic educational institutions to holistically strengthen students’ character.